2018
DOI: 10.1093/nutrit/nuy021
|View full text |Cite
|
Sign up to set email alerts
|

Role of soybean-derived bioactive compounds in inflammatory bowel disease

Abstract: Inflammatory bowel disease (IBD) is a chronic, inflammatory condition of the gastrointestinal tract. Patients with IBD present with debilitating symptoms that alter the quality of life and can develop into severe complications requiring surgery. Epidemiological evidence indicates Westernized societies have an elevated IBD burden when compared with Asian societies. Considering the stark contrast between the typical Western and Eastern dietary patterns, it is postulated that differences in food and lifestyle con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 180 publications
0
15
0
Order By: Relevance
“…In raw soybeans used in this study, 12 isoflavones are identified, including three aglycones (daidzein, genistein, and glycitein) and nine glucosides (namely, three acetyl, three malonyl, and three nonacylated isoflavone β ‐glucosides). When soybeans are processed into products such as tofu and soy milk, their isoflavone aglycone contents increase, while their glucoside contents decrease (Juritsch & Moreau, ). Previously, isoflavone aglycones were reported to be less stable at alkaline pHs than at acidic or neutral pHs (Yatsu, Koester, & Bassani, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In raw soybeans used in this study, 12 isoflavones are identified, including three aglycones (daidzein, genistein, and glycitein) and nine glucosides (namely, three acetyl, three malonyl, and three nonacylated isoflavone β ‐glucosides). When soybeans are processed into products such as tofu and soy milk, their isoflavone aglycone contents increase, while their glucoside contents decrease (Juritsch & Moreau, ). Previously, isoflavone aglycones were reported to be less stable at alkaline pHs than at acidic or neutral pHs (Yatsu, Koester, & Bassani, ).…”
Section: Discussionmentioning
confidence: 99%
“…Malonyl isoflavones have been reported to be more stable than acetyl isoflavones, especially under acidic conditions (Mathias et al., ). Nevertheless, the isoflavone β‐glucosides with malonyl moieties can decrease during extraction, processing, and storage, causing their corresponding β‐glucosides and aglycones to increase (Juritsch & Moreau, ; Rostagno et al., ). Under alkaline conditions, interconversions were observed more commonly for acetyl isoflavones than for malonyl isoflavones (Mathias et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, among Asian populations, high isoflavone intake (much higher than for European populations) is indicated to be associated with the development of the disease [19], suggesting that both studied isoflavone and applied dosage may significantly influence the observed effect. It is emphasized that some preclinical evidence suggests that isoflavones have the potential to improve the prognosis of inflammatory bowel diseases [20]. Taking this into account, there is need to assess the various subclasses in order to translate the current knowledge from preclinical models into further studies and dietary recommendations [12].…”
Section: Introductionmentioning
confidence: 99%